Impaired T-Lymphocyte Responses During Childhood Staphylococcus aureus Infection. (19th June 2021) - Li, Zhaotao; Beesetty, Pavani; Gerges, George; Kleinhenz, Maureen; Moore-Clingenpeel, Melissa; Yang, Ching; Ahmed, Luul B; Hensley, Josey; Steele, Lisa; Chong, Anita S; Montgomery, Christopher P
Abstract: Background: Staphylococcus aureus infections are common throughout the lifespan, with recurrent infections occurring in nearly half of infected children. There is no licensed vaccine, underscoring the need to better understand how S. aureus evades protective immunity. Despite much study, the relative contributions of antibodies and T cells to protection against S. aureus infections in humans are not fully understood. Methods: We prospectively quantified S. aureus -specific antibody levels by ELISA and T-cell responses by ELISpot in S. aureus -infected and healthy children. Results: S. aureus -specific antibody levels and T-cell responses increased with age in healthy children, suggesting a coordinated development of anti-staphylococcal immunity. Antibody levels against leukotoxin E (LukE) and Panton-Valentine leukocidin (LukS-PV), but not α-hemolysin (Hla), were higher in younger infected children, compared with healthy children; these differences disappeared in older children. We observed a striking impairment of global and S. aureus -specific T-cell function in children with invasive and noninvasive infection, suggesting that S. aureus -specific immune responses are dysregulated during childhood infection regardless of the infection phenotype. Conclusions: These findings identify a potential mechanism by which S. aureus infection actively evades adaptive immune responses, thereby preventing the development of protective immunity and maintaining susceptibility to recurrent infection. Abstract : S. aureus infections are common and frequently recur. In this study, severely impaired T-cell responses were observed during childhood infection. This may be a mechanism by which S. aureus evades protective immunity, thereby maintaining susceptibility to recurrent infection.